Hydrogen production from animal waste: comparative analysis and techno-economic evaluation - T. T. Olugasa; E. A. Nasamu; T. I. Banji; M. L. Adekanbi (Discover Energy)
Abstract Factors such as population growth and the depletion of fossil fuel reserves necessitate the development of alternative fuels that are emission-free and offer good combustion performance. Hydrogen is a renewable fuel with high energy potential and zero emissions. Research indicates that biohydrogen can be produced from the biogas generated by the fermentation of agricultural wastes. Biogas steam reforming is a viable method for hydrogen production with efficiency levels similar to natural gas steam reforming. In this study, cow dung, poultry manure, and swine manure were collected from the University of Ibadan Teaching and Research Farm. The pH, moisture content, ash content, total solids (TS), volatile solids (VS), cellulose, protein, and calorific values were determined. The process was simulated using Aspen Plus software. An anaerobic digester with a working volume of 100 $$m^3$$ m 3 was utilized. The biogas produced was upgraded and passed through a steam reformer to produce hydrogen. The daily biogas generation rates from cattle, poultry, and swine were 4605 ls, 4647 ls, and 4437.3 ls respectively, all at a retention time of 21 days. Poultry manure exhibited the highest potential for biogas production, with the optimal temperature for biogas generation being $$56^° \hbox {C}$$ 56 ∘ C . The corresponding hydrogen yields from cattle, poultry, and swine were 396 ls/day, 400.8 ls/day, and 381.6 ls/day respectively. The techno-economic evaluation conducted using Aspen Plus revealed a total capital cost of 10,260,370 USD for hydrogen production. From 1590.4 kg/year of biogas, 274.1 kg/year of hydrogen and 1337.5 kg/year of CO $$_2$$ 2 were produced. The revenue from hydrogen sales amounted to 3015.1 USD. The evaluation concluded that the steam reforming method for hydrogen production is not cost-effective, despite the feedstock being derived from animal wastes. Graphical Abstract